GAMBARAN FAKTOR-FAKTOR PENYEBAB PERNIKAHAN DINI DI DESA PAKISAN KECAMATAN TLOGOSARI KABUPATEN BONDOWOSO - Dina Nur Oktavia; Mashun; Herlidian Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
Marriage is a physical bond between a man and a woman as a husband and wife with the aim of forming a happy family (household). Apart from lack of knowledge resulting from low education, all women who marry at an early age are 53 married women who is in Pakisan Village, Tlogosari Subdistrict, Bondowos Regency. Research Purpose: To determine the factors that cause early marriage in Pakisan Village, Tlogosari Subdistrict, Bondowoso Regency in 2013. This study uses a descriptive survey method with cross-sectional approach. The population in this study is all women who had early marriage in 2013 were 53 people, and 53 samples were also taken. This research was conducted in Pakisan Village, Tlogosari Subdistrict, Bondowoso Regency, conducted on September 22 to September 27, 2014. Data collection was done by distributing questionnaires Research Results: from the results of 53 respondents obtained, that respondents (66.03%) education level was in the middle category first, (62.27%), have less knowledge about early marriage, (73.59%) of respondents have less income and (88.68) are in the category of traditional culture. Of the 53 respondents who sampled the results of the study it can be concluded that the causes Early marriage is the most dominant culture. Suggestion: the results of the study found the factors causing it is wrong Stunya education in junior high school level, etc. according to researchers, better socialization about early marriage such as counseling is held for the community so that people's mindsets can be changed and more advanced